Social Dynamics in the Suroan Tradition: an Anthropological Study of Religious Moderation among Javanese Muslims in Kediri - Ummu Abiha Al Zahra’ (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2024)
This article aims to understand and analyse how the Suroan tradition functions within the context of religious moderation and the social dynamics of the Islamic Javanese community in Kediri. The Suroan tradition is a significant ritual among the Muslim community in Java, carrying profound social and spiritual meaning. Using an anthropological approach, this study examines the social elements influencing the Suroan ritual, including the values embedded within its practices. The findings indicate that Suroan serves not only as an expression of gratitude to God but also as a medium for strengthening solidarity among community members, building cultural identity, and fostering interreligious tolerance. This tradition reflects the community’s ability to adapt and uphold the values of moderation in the face of social change. This research aims to offer new insights into the interaction between local traditions and religious moderation within the Islamic community in Java.